The imaging diagnosis of craniocerebral trauma. The general concepts. - Martins, O (1994)
The author makes a concise review of the imagiology of acute head trauma. The relative value of the various imaging techniques and the present importance of skull radiography are discussed; the role of computed tomography (CT) is emphasized. The most important aspects of traumatic lesions, as evaluated by CT, are presented.